Political unrest under IMF programmes: labour mobility, fiscal conditionality, and democratic representation - Metinsoy, S (2017)
What triggers political unrest under International Monetary Fund (IMF) programmes? Why do we see unrest—protests, strikes, and riots—in some countries under IMF programmes and not in others? This thesis argues that IMF labour conditionality in an immobile labour market compounded by intrusive fiscal conditionality and blocked democratic channels result in unrest. Where labour is immobile in the borrowing country, IMF labour conditionality decentralising the market creates large-scale grievances among the labour groups. Immobile labour groups substantially lose income and benefits under those measures due to high wage differentials and varied labour protection measures across sectors. Moreover, uncertainty and risks increase, while the opportunities to return back to employment or to maintain the existing income and benefits diminish. When the political authority is unable to address the rising grievances due to tight fiscal conditionality and blocked democratic channels, we observe political unrest under IMF programmes. Where labour is mobile, on the other hand, it is easier for workers to switch between sectors and jobs when the economic crisis hits their sector. The labour groups respond to the internal crisis and the external impact by increasing mobility and switching to the sectors that are still growing despite the crisis. Labour conditions do not give rise to a similar degree of uncertainty and risks compared to immobile markets. Hence, programmes are implemented without large-scale unrest. The study tests this theory in a global sample of 117 countries between 1970 and 2013 and investigates the impact of mobility and IMF conditionality on unrest with a data set originally compiled and coded for this study. It then delves into two extreme cases, Greece, 2010 and Turkey, 2001. While Greece had extreme immobility and received intrusive labour and fiscal conditionality in 2010, Turkey is located on the opposite end of the spectrum, with very high levels of mobility, the limited number of labour conditions, and greater fiscal space. We see that while Greece witnessed large-scale unrest in 2010, Turkey implemented the programme smoothly. Finally, the study applies the theory into three shadow cases, Ireland, 2010, Latvia, 2008, and Portugal, 2011 and demonstrates that the varied degrees of mobility and conditionality and fiscal conditionality result in different degrees of unrest.